Precarização e relações de prazer e sofrimento do trabalho dos oficiais de justiça do Amazonas no contexto da Covid-19 - Silva, Alexia Macedo da (Brasil, 2022)
Exercising work activities has become part of the human experience, fostering aspects identities and guiding health and illness conjunctures. Throughout history, the meaning of work has changed many times and, depending on the circumstances, working can be something pleasurable or source of psychological distress. The bailiff is known as the judge's hand on the streets and their work is permeated by particularities and psychosocial risks. The purpose of this research was to identify in the speech of the justice officers of the state of Amazonas in the light of the Psychodynamics of Work, its processes of precariousness of work, as well as the main sources of pleasure and suffering experienced in their journeys through the pandemic context. THE methodology involved conducting a conversation circle in the remote modality with five (5) professionals of the category located in the capital Manaus and in the interior of the state, performing literal transcription of the speeches, manual separation of the categories of analysis and, subsequent analysis of content from Bardin. The results obtained revealed a greater amount of verbalizations directed to suffering, with regard to the topics: lack of recognition by the leadership superior, work overload, logistical difficulties to fulfill orders, as well as as psychic and emotional issues aggravated by the Covid-19. It was observed that the sources of pleasure, although less present, were translated into the self-recognition of importance of the profession, the flexibility of working hours and the remuneration obtained.